Mean blood glucose‐independent HbA1c racial disparity and iron status in youth with Type 1 DM. Issue 4 (10th March 2020) - Hamdan, Mahmoud Adeeb; Gomez, Ricardo; Chalew, Stuart A.
Abstract: Introduction: Black patients have higher HbA1c than Whites even after adjustment for mean blood glucose (MBG). Decreased iron status has been associated with increased HbA1c independently of glucose. We hypothesized that decreased iron status might account for higher HbA1c in Black patients. Methods: Pediatric patients with T1D in the Diabetes Center at Children's Hospital of New Orleans who self‐identified as either Black or White were recruited for the study. At the time of their clinic visit labs were obtained for ferritin (Fer), soluble transferrin receptor (sTfR), HbA1c, and CBC. MBG was derived from patient's home glucose meter records over the last 30 days. Total body iron (TBI) and sTfr/log10 Fer (R/lFer) were calculated. Results: A total of 80 (35 Blacks/45 Whites; 41 female/39 male) patients were recruited. Unadjusted levels of HbA1c, MBG, sTfR, Fer, RDW‐CV, and RDW‐SD were all higher in Blacks than Whites. TBI and R/lFer were not different between groups. Fer was correlated with Hb, MBG but not HbA1c. sTfR was correlated with HbA1c, MCV, MCH, and RDW‐SD. In multiple variable analysis with HbA1c as the dependent variable, race and MBG were statistically significant in the model. However, measures of iron status: Fer, sTfR, R/lFer and TBI were not statistically influential. Conclusion: After adjustment for race, MBG and RDW‐CV, iron indices were not statistically significant independent predictors of HbA1c levels. These observations indicate that factors besides iron status and CBC indices contribute to MBG‐independent racial disparity in HbA1c.